Turkish University Libraries During Novel Coronavirus (COVID-19) Pandemic - Çimen, Ertuğrul; Gürdal, Gültekin; Çuhadar, Sami; Akbaytürk Çanak, Tuba (Information World, 2020)
The goal of this study is to identify how the university libraries responded to Novel Coronavirus ( COVID-19) Pandemic. While some libraries were locked down for this period, some other libraries only limited their services as needed. To provide a full framework, the efforts pertaining this period from the shareholders of university libraries such as publishers and professional associations have also been studied. The second goal of this study is to find out how libraries are ready to adapt themselves to such unexpected situations and adopt remote service models with their existing personnel, collections, budget or infrastructure. A survey is prepared to be sent out to 209 (129 State universities, 75 foundation universities and 5 foundation vocational schools) higher education institutions. The survey was filled out by 84 institutions. The survey results will be analyzed using Surveey.com and MS Excel. At the closing, since Turkey starts easing coronavirus containment measures, recommendations on how libraries should plan their reopening will be shared.